Characteristics of impaired endothelium-dependent relaxation of rat aorta after streptozotocin-induced diabetes. - Shen Jian-zhong; Zheng Xiu-feng (Acta Pharmacologica Sinica, 2016)
AIM: To study whether impaired endothelium-dependent relaxation (EDR) in early diabetic mellitus in response to different receptor-mediated and nonreceptor-mediated vasodilators ran parallel and its possible mechanism. METHODS: Isometric tension recording in aortic rings from streptozotocin (Str)-induced diabetic and age-matched nondiabetic rats. RESULTS: EDR induced by receptor agonist acetylcholine (ACh), histamine (His) or bradykinin (BK) were all significantly reduced in diabetic rings compared with control rings, whereas nonreceptor agonist calcimycin-induced EDR was well reserved in diabetic rings [IC50 control: (0.13 +/- 0.07) mumol.L-1 diabetic: (0.14 +/- 0.06) mumol.L-1, P > 0.05, n = 7]. Cyclopiazonic acid (CPA) which also is a nonreceptor mediated endothelium-dependent vasorelaxant and cells' capacitative Ca2+ entry stimulant, failed to trigger EDR in diabetic rings. Pretreatment with N omega-nitro-L-arginine methylester (L-NAME, 0.3 mmol.L-1) not only abolished all of the EDR elicited by above mentioned vasodilators in either of diabetic or control rings, but also leveled responses triggered by each of the agonists between diabetic and control rings. Upon the maximal EDR induced by ACh (1 mol.L-1) or CPA (3 mumol.L-1) in phenylephrine (1 mumol.L-1) precontracted rings, calcimycin (1 mumol.L-1) further relaxed diabetic rings, but contracted control preparations. When endothelium was denuded, relaxation evoked by sodium nitroprusside and contractions triggered by CPA or His were all identical between diabetic and control rings. CONCLUSION: Receptor agonists but not nonreceptor agonists-induced EDR are commonly impaired in 4-wk Str-induced diabetic rat aorta, and this defective effect is attributable to the low formation of EDRF/NO which is related to impaired capacitative Ca2+ entry pathway in endothelium.